Study the Effects of Annona sp. Extract on Some Physiological Parameters and Fertility in Diabetic Mice - Ibraheem, Shaima R.; Ahmed, Enas Shehab; Mahmoud, Zainab Fakad; Abid Al-Bari, Hazim Ismail (Iraqi Journal of Science, 2024)
The current study was conducted to investigate Annona fruit pulp effects on the levels of various physiological biomarkers linked with insulin-dependent diabetes mellitus after disease induction in mice, as well as indications of oxidative stress and male hormones. The rats were separated into four groups, three of which were given Alloxan (90 mg/kg body weight) to induce diabetes, while the fourth served as a negative control. The first group of diabetic mice received no therapy, the second received metformin (600 mg/kg body weight) and the third received Annona fruit puree. The mice were sacrificed at the end of the experiment, to acquire blood and tissue samples from the liver, kidneys and spleen. The first untreated group showed a drop in insulin, good fats (High-density lipoprotein-HDL), antioxidant markers (Superoxide dismutase (SOD) and catalase –(CAT)), testosterone and follicle stimulating hormone-FSH, as well as an increase in glucose and low-density lipoprotein (LDL), triglyceride (TG), total cholesterol (TC), and luteinizing hormone (LH). Giving diabetic mice in groups 2 and 3 metformin and Annona puree improved the physiological markers levels, bringing their values closer to normal. The results indicated that the treatment with Annona fruit pulp had more protective effects than metformin. The histological findings confirmed the role of Annona fruit in improving the health indicators and the structural condition of the vital organs represented in the liver, kidneys and spleen of diabetic mice.